Disciplinary traditions and the dissemination of knowledge : An international comparison of publication patterns in journals of education - Ertl, Hubert [Verfasser]; Zierer, Klaus [Verfasser]; Phillips, David [Verfasser]; Tippelt, Rudolf [Verfasser] (My University, 2015)
"This paper presents findings from two studies of publication patterns in leading English, German, European and US journals of education. The studies were funded by the German Research Association and conducted by an international team of researchers. All papers published in 14 selected journals between 2001 and 2010 were analysed in terms of their author profile, their methodological approach and their thematic focus. The analyses resulted in publication patterns for the selected journals and at an aggregated level for the four geographic areas in which journals are published, highlighting many similarities, but also distinct differences. As far as the differences are concerned, the lower share of female authors and the relative low proportion of papers drawing on empirical research in German journals are noteworthy. For US journals, the comparatively low importance of papers drawing on the international research discourse seems to be particularly important. Based on an analysis of related studies in this field the paper demonstrates a degree of alignment of publication patterns with disciplinary traditions and formation processes in the field of education. However, the trend analysis provided also shows that some of the traditional boundaries of education as an academic discipline are in a state of flux." (authors' abtract; BIBB-Doku)
Keywords: T 4.9 Pädagogik; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Erziehungswissenschaft; Bildungsforschung; Publikationsverhalten; Bibliometrie; Internationaler Vergleich